2013
DOI: 10.1371/journal.pmed.1001468
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Health Care Delivery and Data Collection in Rural India Using a Rapidly Deployable eHealth Center

Abstract: Anurag Agrawal and colleagues describe their experience of setting up a readily deployable cargo container-based health center in rural India. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The most common disease areas were either diabetes (n=8) [20][21][22][23][24][25][26][27] or CVD and risk factors for CVD (n=9) [22,[28][29][30][31][32][33][34][35]. Thirteen studies tested specific mHealth interventions, but only seven used a RCT design [23,25,26,33,[36][37][38], with the remainder using quasi-experimental designs to assess outcomes [24,27,28,34,39,40]. Six exploratory studies were identified which described, validated, or pilot-tested various mHealth interventions but did not provide any substantive outcome data [29][30][31][32][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common disease areas were either diabetes (n=8) [20][21][22][23][24][25][26][27] or CVD and risk factors for CVD (n=9) [22,[28][29][30][31][32][33][34][35]. Thirteen studies tested specific mHealth interventions, but only seven used a RCT design [23,25,26,33,[36][37][38], with the remainder using quasi-experimental designs to assess outcomes [24,27,28,34,39,40]. Six exploratory studies were identified which described, validated, or pilot-tested various mHealth interventions but did not provide any substantive outcome data [29][30][31][32][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Of the intervention and exploratory studies (n=19), the following mHealth domains were identified: client education and behavior communication (n=13) [23-27, 33, 34, 36-41], sensors and diagnostics (n=5) [28-30, 32, 35], registries (n=1) [34], data collection (n=3) [28,29,34], electronic health records (n=1) [28], decision support (n=1) [31], provider communication (n=3) [28,29,34], provider workplanning (n=5) [28,[36][37][38]40], and supply chain management (n=1) [28]. There were no studies pertaining to provider training and education, human resource management, or financial transactions and incentives.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary focus of the Health care centers is Infant immunization programs, Anti epidemic programs, Birth control, Pregnancy and Health Care. By Adopting E-Health technologies we can reduce the overwhelming burden on hospitals [1]. It refers to digital services used in Healthcare.…”
Section: Introductionmentioning
confidence: 99%